Prevalence of asymptomatic radiographic vertebral fracture in postmenopausal Thai women - Chatlert Pongchaiyakul (2020)
© 2020, International Osteoporosis Foundation and National Osteoporosis Foundation. Summary: We aim to investigate the nationwide prevalence of asymptomatic radiographic vertebral fracture in Thailand. We found 29% of postmenopausal women had at least one radiographic vertebral fracture. The prevalence was significantly higher among women with osteoporosis at the total hip (TH) region which implies that TH bone mineral density is a determinant of vertebral fracture risk. Introduction: Radiographic vertebral fracture is associated with an increased risk of osteoporotic fracture and mortality in postmenopausal women. We designed a study to determine the prevalence of asymptomatic vertebral fractures in postmenopausal Thai women. Methods: The study was designed as a cross-sectional investigation at five university hospitals so as to achieve representation of the four main regions of Thailand. Radiographs were taken from 1062 postmenopausal women averaging 60 years of age. The presence of vertebral fracture was assessed by the Genant’s semiquantitative method with three independent radiologists. Respective bone mineral density was measured by dual-energy X-ray absorptiometry (DEXA) at the lumbar spine (LS), femoral neck (FN), and total hip (TH). Results: Among the 1062 women, 311 were found to have at least one radiographic vertebral fracture—yielding a prevalence of 29% (95% CI 23.6–32.0%)—and 90 (8.5%, 95% CI 6.8–10.2%) had at least two fractures. The prevalence of vertebral fracture increased with advancing age. Most fractures occurred at one vertebra (71%) and only 29% at multiple vertebrae. The prevalence of vertebral fracture was significantly higher among women with osteoporosis compared with non-osteoporosis at the TH region. There was no significant difference in the prevalence among women with or without osteoporosis at the LS or FN. Conclusions: Radiographic vertebral fractures were common among Thai postmenopausal women (~ 29%). These findings suggest that approximately one in three postmenopausal women has undiagnosed vertebral fracture. Radiographic diagnosis should therefore be an essential investigation for identifying and confirming the presence of vertebral fractures.